Physical, social, and psychological characteristics of community-dwelling elderly Japanese dog and cat owners - Taniguchi, Yu; Seino, Satoshi; Nishi, Mariko; Tomine, Yui; Tanaka, Izumi; Yokoyama, Yuri; Amano, Hidenori; Kitamura, Akihiko; Shinkai, Shoji (PLOS ONE, 2018)
Objectives Previous studies examined the physical characteristics of older dog owners. However, associations of health-related factors with dog/cat ownership have not been comprehensively evaluated. This cross-sectional study examined physical function, physical activity, social function, and psychological function of a population of community-dwelling older Japanese dog and cat owners after controlling for important confounders. Methods The analysis included data from 11,233 community-dwelling adults aged 65 years or older (51.5% women; 52.3% aged 75–84), in Ota City, Tokyo, Japan. Pet ownership experience and pet species owned were determined by self-reported questionnaire, and current, past, and never dog/cat ownership was analyzed. Results Analysis of variables related to physical function and physical activity showed that motor fitness scale and walking activity were significantly associated with experience of dog ownership, after adjustment for important sociodemographic and health characteristics. Analysis of social function showed that interaction with neighbors, social isolation, and trust in neighbors were significantly associated with experience of dog ownership and cat ownership. Conclusions As compared with respondents with no history of pet ownership, motor fitness and walking activity are greater for dog owners and social function is higher for dog and cat owners. Caring for a dog or cat might be an effective health promotion strategy to increase physical activity and facilitate social participation among older adults.